Successful teamwork of a sewing thread industry in Bangladesh: a study on Coats Bangladesh Ltd. - Faruk, Md. Omar (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.